1983
DOI: 10.1002/ajh.2830150409
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory abnormalities in evans syndrome

Abstract: Immune function in six patients with Evans syndrome (Coombs-positive hemolytic anemia and immune thrombocytopenia) was compared to that in seven with chronic ITP. The two groups differed in measurements of T-cell subsets and immunoglobulin production. Evans syndrome patients had decreased T4 (T-helper) (P = 0.025), increased T8 (T-suppressor) (P = 0.008), and a decreased ratio of T4:T8 cells (P = 0.0009) when compared to controls. Results in chronic ITP patients were similar to those in controls. Serum IgG, Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 30 publications
1
53
1
1
Order By: Relevance
“…7 Immune abnormalities, intrinsic to the disease and/or to chronic immune suppression, are associated with Evans syndrome. 8 This patient's course demonstrated numerous opportunistic infections mandating pre-, peri-and posttransplant anti-microbial therapy.…”
Section: Discussionmentioning
confidence: 90%
“…7 Immune abnormalities, intrinsic to the disease and/or to chronic immune suppression, are associated with Evans syndrome. 8 This patient's course demonstrated numerous opportunistic infections mandating pre-, peri-and posttransplant anti-microbial therapy.…”
Section: Discussionmentioning
confidence: 90%
“…More recently, the spectrum of the disease has broadened, especially in children, and there is increasing evidence to suggest that ES reflects a state of profound immune dysregulation as opposed to a coincidental combination of immune cytopenias. 16 To better define the clinical spectrum of adult ES, we have analyzed retrospectively the data from 68 adults with a well-defined ES seen in the departments of internal medicine or hematology of 8 major institutions in France and Italy. Despite the possible bias because of the retrospective design of the study and because the number of patients remains too small to point out many statistically significant differences between subgroups, this analysis gives a new insight into adult ES.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al [17]demonstrated decreased CD4 and increased CD8 circulating lymphocyte populations in Evans syndrome [17]. Also, the BAL pattern of BOOP is characterized by a decreased CD4/CD8 ratio with predominant CD8 lymphocytes [18].…”
Section: Discussionmentioning
confidence: 99%